A review on natural fiber-reinforced geopolymer and cement-based composites - Molano Camargo, Marfa Carolina; Taye, Eyerusalem; Roether, Judith; Redda, Daniel Tilahun; Boccaccini, Aldo R. (Materials, 2020)
The use of ecological materials for building and industrial applications contributes to minimizing the environmental impact of new technologies. In this context, the cement and geopolymer sectors are considering natural fibers as sustainable reinforcement for developing composites. Natural fibers are renewable, biodegradable, and non-toxic, and they exhibit attractive mechanical properties in comparison with their synthetic fiber counterparts. However, their hydrophilic character makes them vulnerable to high volumes of moisture absorption, thus conferring poor wetting with the matrix and weakening the fiber–matrix interface. Therefore, modification and functionalization strategies for natural fibers to tailor interface properties and to improve the durability and mechanical behavior of cement and geopolymer-based composites become highly important. This paper presents a review of the physical, chemical and biological pre-treatments that have been performed on natural fibers, their results and effects on the fiber–matrix interface of cement and geopolymer composites. In addition, the degradation mechanisms of natural fibers used in such composites are discussed. This review finalizes with concluding remarks and recommendations to be addressed through further in-depth studies in the field.
CRIS-Team Scopus Importer:2020-11-13
Keywords: Composites; Fibers; Geopolymers; Interphases; Surface treatments